Aplikasi Penerimaan Siswa Baru Berbasis Web Di Yayasan Al-Qaaf Tangerang Banten - Pebrianto; Pratama, Gilang; Pratama, Dandi; Haryono, Wasis (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The online student registration system at the Al-Qaaf Foundation is an effective solution to overcome registration problems that are usually done manually. Based on research and testing, 90.25% of respondents stated that this application is very suitable to help users in managing enrollment data in schools. This shows that the majority of respondents feel that this system is useful and able to meet their needs. However, 9.75% of respondents indicated that the app still needs further development, indicating that there are some shortcomings or features that need to be improved or added. Input from respondents who feel the need for development can be the basis for making improvements and improvements to the system. Overall, the use of the registration system at the Al-Qaaf Foundation can provide benefits in the management of student registration data. However, it is important to continue to evaluate, develop, and improve the system so that it can continue to meet user needs and contribute optimally in the field of education.